PENGEMBANGAN MATERI FIKIH KELAS VIII MADRASAH TSANAWIYAH: TENTANG INDAHNYA BERPUASA - Khoirul Huda, Abdul Karim (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2019)
This article aims to find out anything in the depth and breadth of the fasting material in class VIII Madrasah Tsanawiyah. The method used in this research is literature study, data collected through student books and fikih class VIII Madrasah Tsanawiyah teacher books, as well as treatment with the results of previous studies related to material development, then analyzed and described. The results of this study indicate that the subject matter contained in the eighth grade students’ printed books of the subjects in the fasting chapter is still not broad and deep, so that teachers are expected to develop material that will apply it by paying attention to the requirements for developing, namely, facts, concepts, principles. , and procedures, then the four conditions must have the following things, namely distinctive, functional, valuable, and easy to use. This is an alarm so that students do not stutter about the development of science and technology and are able to keep up with the religious knowledge that has been learned. The expected positive impact of research activities by revising and developing fiqh subject matter, namely fiqh material is different from the previous one, it is more weighty, functional and easy to apply for teachers and students.